The history of the Romanian University of Cluj, in the documents of a private archive - Ioana Bot; Ionucu Pop (University Babes-Bolyai, 2022)
The present study was started on the basis of the documents contained in a private archive, transferred in 2004 into the property of the Romanian state and currently located in the Special Collections section of the "Octavian Goga" Cluj County Library. These are Dumitru Popovici's (1902-1952) personal and professional documents, professor of the history of Romanian literature at the University of Cluj from 1936 until his death, one of the most important Romanian literary historians of the interwar period, author of important studies concerning the Enlightenment, Romanticism and modern Romanian literature. Safekept by his family, many of the documents in Popovici's personal archive manage to complete sequences of the history of Romanian university life, where the Communist Regime, with its various purges, destroyed the archives of official institutions. Based on these documents, and through a careful reconstruction of the life of the professor, new perspectives on various aspects of the Romanian intellectual history of the last century are opened: the history of several Romanian academic ad cultural institutions, the history of various university disciplines and specialisations, the personal history of an important university figure in the transformation of the Romanian academic space etc.